Potential effect of Irisin on sarcopenia: a systematic review - Yixiao Chen; Min Qian; Feng Gao; Guoqing Li; Kangzu Peng; Qingnan Sun; Yifei Sun; Gang Liu; Yufeng Ge; Minghui Yang; Xinbao Wu (BMC Musculoskeletal Disorders)
Abstract Objective Sarcopenia, a progressive musculoskeletal disorder associated with aging, is characterized by the deterioration of muscle mass, strength, and physical performance. This condition significantly increases the risk of debilitating consequences including functional impairment, diminished life quality, and increased mortality. With the progress of aging, it will affect a large number of people in the world and bring many problems. Despite its clinical significance, there are no medicine used to treatment sarcopenia by FDA approval in clinical. This systematic review synthesizes current evidence on the diagnostic and therapeutic potential of irisin—a myokine induced by exercise—in sarcopenia, aiming to address two key questions: (1) Can irisin serve as a reliable biomarker for sarcopenia diagnosis? (2) Does irisin hold promise as a therapeutic agent for sarcopenia management? Methods A comprehensive literature search was conducted across multiple databases (Web of Science, PubMed, Cochrane Library, and Embase) to examine the relationship between irisin and sarcopenia. Eligible studies meeting our inclusion criteria underwent rigorous quality assessment. Result 364 studies were identified, of which only 21 met the inclusion criteria—12 involving human studies and 9 involving animal and cell experiments. In human studies, irisin may serve as a potential diagnostic marker for sarcopenia in the elderly and postmenopausal women. In addition, as a myokine of exercise induced, increased circulating levels of irisin may enhanced skeletal muscle mass. Moreover, animal and cellular experiments suggest that increased levels of irisin help improve muscle mass. Conclusion In conclusion, this review indicates that irisin has potential therapeutic effects for sarcopenia and may become a promising treatment for sarcopenia in the future. However, there is currently a lack of high-quality studies on the use of irisin in treating sarcopenia, and the relevant mechanisms of action are not yet clear. Therefore, more studies are needed to clarify the relationship between irisin and sarcopenia in the future.